The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1364/oe.390538
|View full text |Cite
|
Sign up to set email alerts
|

Tunable mid-wave infrared Fabry-Perot bandpass filters using phase-change GeSbTe

Abstract: We demonstrate spectrally-tunable Fabry-Perot bandpass filters operating across the MWIR by utilizing the phasechange material GeSbTe (GST) as a tunable cavity medium between two (Ge:Si) distributed Bragg reflectors. The induced refractive index modulation of GST increases the cavity's optical path length, red-shifting the passband. Our filters have spectral-tunability of ~300 nm, transmission efficiencies of 60-75% and narrowband FWHMs of 50-65 nm (Q-factor ~70-90). We further show multispectral thermal imagi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 41 publications
0
50
0
Order By: Relevance
“…Note that there also other options for MEMS tunable filters based on the thickness actuation of solid components of the filter [ 57 ]. However, this review focuses on the thickness actuation of an airgap cavity.…”
Section: Fabrication and Characterization Of Mems Tunable Fp Filtementioning
confidence: 99%
See 1 more Smart Citation
“…Note that there also other options for MEMS tunable filters based on the thickness actuation of solid components of the filter [ 57 ]. However, this review focuses on the thickness actuation of an airgap cavity.…”
Section: Fabrication and Characterization Of Mems Tunable Fp Filtementioning
confidence: 99%
“…The third interferometric spectrometer is based on the Fabry–Pérot (FP) principle [ 4 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. Although only two parallel transparent dielectric mirrors are involved, the FP interferometer is also highly complex and involves multipath interference.…”
Section: Introductionmentioning
confidence: 99%
“…This concept was pursued by integrating a subwavelength optical cavity, which incorporated two separated layers of GeTe, with a joule heater element to produce a tunable micro-display rendering four different colors [171]. Also, more recently multispectral thermal imaging and gas sensing have been demonstrated in the mid-wave IR range by tuning the GST spacer between two cascaded Ge:Si distributed Bragg reflectors [172].…”
Section: Hybrid Dielectric/pcm Metasurfaces For Global Amplitude Controlmentioning
confidence: 99%
“…Ding et al [ 17 ] also proposed tunable bandstop mid-infrared filters based on Ge Sb Te metasurface composed of nanorods. In order to achieve bandpass filters, Zhou et al [ 18 ] and Williams et al [ 19 ] respectively proposed or demonstrated tunable mid-infrared bandpass filters by embedding a Ge Sb Te film in a Fabry-Pérot cavity. Although the quality factor, defined as the ratio of the linewidth to the central wavelength, can reach 70–90, the spectral tunability is very limited (only ∼420 nm in [ 18 ] or ∼300 nm in [ 19 ]).…”
Section: Introductionmentioning
confidence: 99%